GenAI-Augmented Data Analytics in Screening and Monitoring of Cervical and Breast Cancer: A Novel Approach to Precision Oncology - Rodriguez, Marcus; Rahman, Kawsher; Devarapu, Krishna; Sridharlakshmi, Narayana Reddy Bommu; Gade, Pavan Kumar; Allam, Abhishekar Reddy (Engineering International, 2023)
This research examines how Generative Artificial Intelligence (GenAI) might improve cervical and breast cancer screening and monitoring data analytics to improve diagnosis accuracy and patient care in precision oncology. We evaluate literature and secondary data to show how GenAI technologies, including improved imaging analysis, genetic data integration, and predictive modeling, might improve early diagnosis and patient care. Significant results show that GenAI improves imaging analysis and genetic insights to personalize treatment approaches, enhancing diagnostic efficiency. However, model interpretability, data bias, and resource restrictions prevented broad deployment. The paper underlines the need for legislative frameworks that support explainable AI, safe data-sharing protocols, and inclusive datasets to guarantee different groups have fair access to GenAI applications. These issues must be addressed for GenAI to enhance cancer treatment, improve patient outcomes, and create a more equitable healthcare system. This study adds to the discussion on AI and oncology and highlights GenAI's potential to enhance precision cancer treatment.
Keywords: Generative Artificial Intelligence (GenAI); Precision Oncology; Breast Cancer; Cervical Cancer; Data Analytics; Cancer Screening; Predictive Modeling